2002
DOI: 10.1002/pds.667
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions as a cause for admissions to a department of internal medicine

Abstract: The prevalence of drug-related problems causing or contributing to admission to a clinic of internal medicine is high and is dominated by type A reactions, i.e. reactions in principle predictable and preventable. This implies a possibility to increase drug safety by preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
125
1
6

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 22 publications
9
125
1
6
Order By: Relevance
“…In the reviewing process, we combined clinical judgment with the use of predetermined triggers, namely combinations of drugs and symptoms or certain "highalert" medications [3][4][5]23,24]. As shown in Figure 2, the initial review, which was performed by a research assistant supported by an experienced clinical pharmacist, was followed by a final review by a multi-professional expert group of senior researchers and clinicians (one clinical pharmacist, one clinical pharmacologist, one consultant in internal medicine/geriatrics and one general practitioner).…”
Section: Drug-related Hospital Revisitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the reviewing process, we combined clinical judgment with the use of predetermined triggers, namely combinations of drugs and symptoms or certain "highalert" medications [3][4][5]23,24]. As shown in Figure 2, the initial review, which was performed by a research assistant supported by an experienced clinical pharmacist, was followed by a final review by a multi-professional expert group of senior researchers and clinicians (one clinical pharmacist, one clinical pharmacologist, one consultant in internal medicine/geriatrics and one general practitioner).…”
Section: Drug-related Hospital Revisitsmentioning
confidence: 99%
“…However, problems associated with drug treatment are frequent among elderly hospitalised patients [1,2] and, for some patients, it can be a drug-related problem that causes the hospital admission [3][4][5]. Many drug-related problems can be solved or prevented; it has been estimated that more than half of the drug-related admissions to hospital are preventable [6].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse drug reactions (ADRs) are a major health care problem and a common cause for hospital care [1][2][3]. Consequently, an analysis of risks and benefits is essential before initializing drug treatment in patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important method for detecting signals, which is one aim of pharmacovigilance. In Sweden, authorized prescribing health care providers (physicians, dentists) and nurses are obliged to report (1) serious ADRs, (2) ADRs not mentioned in the summary of product characteristics (SPC), (3) ADRs related to the use of new drugs (≤2 years on the market) except those labeled as common in the SPC and (4) ADRs whose incidence seems to increase [4], the latter obviously being difficult for any individual to identify. All ADR reports are reviewed by trained nurses (MLJ, GB) and clinical pharmacologists (SMW) at regional pharmacovigilance centers, after which they are entered in the SWEdish Drug Information System (SWEDIS).…”
Section: Introductionmentioning
confidence: 99%
“…Other Swedish population-based studies among people 75 years and older have shown that inappropriate drug use (IDU) is common, with a prevalence of 16.5-19% [8,12]. IDU is associated with adverse drug events (ADEs) and is an important reason for unplanned admittance to hospital of elderly people [8,[16][17][18][19]. The proportion of drug-related hospital admissions has been shown to be up to 6%, with a substantially higher proportion among elderly patients [2,17,18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%